Contemporary Opera in Buenos Aires at the Turn of the Century (Revista Argentina de Musicología, 2020)
Between the 1990s and the present day, Buenos Aires became a city of high visibility for contemporary opera. On the one hand, through local staging of international operas, and on the other, through the commission and production of new works by Argentine composers. In this text we will consider, first of all, the overall “state of things” in the field of the opera in the second half of the twentieth century, to point out then some specificities of the genre in the city of Buenos Aires. Secondly, we will look at the first productions of international operas in the local context to see how these productions were adapted to the local milieu and what was their critical reception. We will especially consider the role of these works in rejuvenating and consolidating new audiences for contemporary music. Finally, we propose a comparative study of three operas whose librettos deal with historical and affective problems of the Chilean and Argentine dictatorships of the 1970s, to assess how different authors address the complex relationship between political violence, memory and musical forms, with the purpose of making visible the critical place that a genre like opera can have in the 21st century.
Keywords: Contemporary Opera; Argentine Music; Music and Dictatorship; Music and Stage